2009
DOI: 10.3904/kjim.2009.24.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Mononucleosis Hepatitis in Young Adults: Two Case Reports

Abstract: Infectious mononucleosis due to Epstein-Barr virus (EBV) infection sometimes causes acute hepatitis, which is usually self-limiting with mildly elevated transaminases, but rarely with jaundice. Primary EBV infection in children is usually asymptomatic, but in a small number of healthy individuals, typically young adults, EBV infection results in a clinical syndrome of infectious mononucleosis with hepatitis, with typical symptoms of fever, pharyngitis, lymphadenopathy, and hepatosplenomegaly. EBV is rather unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 21 publications
2
31
0
2
Order By: Relevance
“…These findings are in agreement with previous studies which show that, although abnormal liver function tests occur in up to 80% of patients with EBV infection, symptomatic hepatitis is uncommon . In contrast to most of the existing literature which describes EBV hepatitis in children and young adults, our findings suggest that EBV hepatitis can occur at any age, including the elderly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with previous studies which show that, although abnormal liver function tests occur in up to 80% of patients with EBV infection, symptomatic hepatitis is uncommon . In contrast to most of the existing literature which describes EBV hepatitis in children and young adults, our findings suggest that EBV hepatitis can occur at any age, including the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of EBV infections occur in childhood and are asymptomatic. Symptomatic disease most commonly presents in young adults with the classic triad of fever, sore throat and lymphadenopathy, known as infectious mononucleosis . It is normally a benign and self‐limiting illness.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of liver involvement in IM patients was unclear, much less in the discrepancy between different age group. CD3 positive T lymphocytes were identified as the main lymphocytic infiltrate in EBV hepatitis, which were mainly cytotoxic CD8 positive T lymphocytes 18-20. Several studies have shown increased level of inflammatory cytokines in the sera of IM patients 10,21.…”
Section: Discussionmentioning
confidence: 99%
“…[6,8] Tek taraflı ve iki taraflı efüzyon yaklaşık olarak eşit sıklıkta görülmektedir. Literatürde enfeksiyoz mononükleoz komplikasyonu olarak pulmoner efüzyon gelişen 12 olgu sunulmuş-tur.…”
Section: Discussionunclassified
“…[5] Primer EBV enfeksiyonunda hepatit genellikle orta derecede seyretmektedir. [6] Pulmoner tutulum hastalarda bilinen bir komplikasyon iken, plevral efüzyon nadirdir. [7] Olgu Sunumu…”
Section: öZetunclassified